2003
DOI: 10.1002/jsfa.1334
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration kinetics of red pepper (Capsicum annuum L var Jaranda)

Abstract: Shredded and whole red pepper samples were dehydrated in a laboratory drier with a through-flow air velocity of 0.5 m s À1 at 50, 55, 60 and 70°C. Shredded peppers dried faster than whole peppers. The drying behaviour of whole samples was characterised by a constant-and a falling-rate drying period, whilst that of shredded samples was characterised by a falling-rate drying period only. The mass transfer coefficient for whole samples during the constant-rate period was computed experimentally. The effect of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 10 publications
9
55
0
11
Order By: Relevance
“…This is due to higher surface area, which enhances the drying efficiency of driers and soft tissue nature, which is useful to remove water from inner tissues to outer wall, of mango and guava than aonla. Similar results have been obtained by several other workers (Akpinar and Bicer 2005;Sanjuan et al 2003;Wang and Xi 2005). The rehydration characteristics of dried products are widely used as the quality index.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This is due to higher surface area, which enhances the drying efficiency of driers and soft tissue nature, which is useful to remove water from inner tissues to outer wall, of mango and guava than aonla. Similar results have been obtained by several other workers (Akpinar and Bicer 2005;Sanjuan et al 2003;Wang and Xi 2005). The rehydration characteristics of dried products are widely used as the quality index.…”
Section: Resultssupporting
confidence: 89%
“…The presence of the clear falling rate period confirmed that the moisture removed was driven internally by energy absorption and the internal mass resistance which controls the drying process. Under such circumstances, it was assumed that water transportation occurs via diffusion (Sanjuan et al 2003). Thin structure and large surface area of prepared fruit slices facilitate rapid loss of moisture and thus a falling rate period.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature dependence of the effective diffusivity may be described by an Arrhenius-type relationship (Madamba et al, 1996;Ozdemir & Devres, 1999;Sanjuan et al, 2003;Akgun & Doymaz, 2005;Wang et al, 2006) and written as:…”
Section: Effective Moisture Diffusivitymentioning
confidence: 99%
“…It decreases faster in the beginning of the drying processes and gradually slowed down through the end (Ben Haj Said et al 2011). Drying curves were characterized by a constant-and a falling-rate drying period (Sanjuán et al 2003;Da silva et al 2013;Rodríguez et al 2014). Allium roseum leaves drying behaviour results of the two mechanisms that involved in the drying process: convection and diffusion (Da silva et al 2013).…”
Section: Experimental Drying Kineticsmentioning
confidence: 99%